2017
DOI: 10.3390/rs9030207
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Downwelling Surface Longwave Radiation under Heavy Dust Aerosol Sky

Abstract: Abstract:The variation of aerosols, especially dust aerosol, in time and space plays an important role in climate forcing studies. Aerosols can effectively reduce land surface longwave emission and re-emit energy at a colder temperature, which makes it difficult to estimate downwelling surface longwave radiation (DSLR) with satellite data. Using the latest atmospheric radiative transfer code (MODTRAN 5.0), we have simulated the outgoing longwave radiation (OLR) and DSLR under different land surface types and a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…They also concluded that dust has a positive radiative effect in the longwave spectrum, both at the Earth's surface and at the top of the atmosphere. Similar conclusions are drawn in the paper by Wang et al (2017), who also studied dust, concluding that the greater its amount in the atmosphere is, the greater its positive radiative effect in the longwave spectrum is. The importance of water vapor in such type of effect assessment is emphasized.…”
Section: Introductionsupporting
confidence: 86%
“…They also concluded that dust has a positive radiative effect in the longwave spectrum, both at the Earth's surface and at the top of the atmosphere. Similar conclusions are drawn in the paper by Wang et al (2017), who also studied dust, concluding that the greater its amount in the atmosphere is, the greater its positive radiative effect in the longwave spectrum is. The importance of water vapor in such type of effect assessment is emphasized.…”
Section: Introductionsupporting
confidence: 86%
“…During the southern hemisphere summer, the bias and RMSE of OLR 4ch and CERES OLR for the area around the Australian desert were 0.37 Wm −2 and 6.52 Wm −2 , which was a decrease 7.46 Wm −2 and 3.73 Wm −2 compared to the difference in the single-channel OLR 1ch and CERES OLR. In regions like the Australian desert, which are dry and have a high surface temperature, changes in OLR are sensitive to absorption gas in the atmosphere [10,[41][42][43][44]; therefore, the OLR calculation algorithm must be built using channel information that can properly reflect these changes. (a,b,c,d), the difference between these two OLR values (e,f,g,h), and the distribution of the differences among OLR 1ch , OLR 2ch , and OLR 4ch (i,j,k,l).…”
Section: Resultsmentioning
confidence: 99%
“…Water vapor is already known as a very important factor in reducing OLR [10,39]. CO 2 also reduces OLR as its concentrations increase continually [40], and there are also studies on OLR reductions caused by O 3 and aerosols [41][42][43][44]. However, these must use channels that are sensitive to absorption gases because there are regional patterns and long-term changes in this factor and increases in the concentration of absorption gases in the atmosphere reduce OLR [15].…”
Section: Introductionmentioning
confidence: 99%
“…In clear-sky conditions, many researchers have used satellite-based radiances measured at TOA to develop different statistical regression methods to estimate DSLR [25][26][27]. Some scholars have modified Tang and Li's [25] method to make it suitable for different situations [28,29], showing that the algorithm is relatively mature. Tang and Li's [25] algorithm is expressed as follows:…”
Section: Estimating Dslr Under Clear-sky Conditionsmentioning
confidence: 99%